Perancangan dan Pembuatan Sistem Infromasi Akuntansi di Perusahaan XYZ - Suseno, Prayudi; Rostianingsih, Silvia; Dewi, Lily Puspa (Jurnal Infra, 2014)
XYZ company is a company engaged in manufacturing car boxes. Box for sale is the result of the manufacture from raw materials purchased from suppliers and then processed by the production. The company want to replace manual systems to computerized systems, because by using the old system of recording transactions are less secure and not convincing in data storage. Thus, they need a system that can help improve company performance. Therefore, in this thesis designed an accounting system that can perform all accounting processes and transactions more quickly and with securely stored data.The process of making this software is started from the system design, analyzes the Problems Company have, and analysis of the needs that exist in the company. The modules are made using of Microsoft Visio for DFD, ERD using Smart Draw and also design tables and design a menu . This software is created using VB programming language .NET and Microsoft SQL Server also uses as data storage.Based on the results of testing, the program is considered to be in accordance with existing accounting system in general. This can be evidenced by the percentage of the number of respondents who answered the questionnaire.